2016
DOI: 10.1097/tp.0000000000001327
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Events and Complications in Minimally Invasive Live Donor Nephrectomy

Abstract: The used techniques for minimally invasive live donor nephrectomy are safe and associated with low complication rates and minimal risk of mortality. These data may be helpful to develop a standardized, donor-tailored informed consent procedure for live donor nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 185 publications
5
61
2
3
Order By: Relevance
“…19 A systematic review and meta-analysis found postoperative complications after minimally invasive nephrectomy occurred in 7.3% of living donors. 20 Also, in a recent national study of nearly 15,000 United States donors, 16.8% of donors experienced a perioperative complication. 21 Moreover, a questionnaire study of donors 3 months after their operation found that 18.5% rated their overall health as "somewhat worse" than before.…”
Section: Disincentive 4: Risk Of Dying From Kidney Removalmentioning
confidence: 99%
“…19 A systematic review and meta-analysis found postoperative complications after minimally invasive nephrectomy occurred in 7.3% of living donors. 20 Also, in a recent national study of nearly 15,000 United States donors, 16.8% of donors experienced a perioperative complication. 21 Moreover, a questionnaire study of donors 3 months after their operation found that 18.5% rated their overall health as "somewhat worse" than before.…”
Section: Disincentive 4: Risk Of Dying From Kidney Removalmentioning
confidence: 99%
“…The currently available techniques for minimally invasive live donor nephrectomy are safe and associated with low complication rates, and minimal risk of mortality. [41]…”
Section: Discussionmentioning
confidence: 99%
“…OPTN data indicates that there were only five donation-related deaths within a year of donation in live donors in 2012 [2]. A recent meta-analysis reported that the mortality rate after live donor nephrectomy was 0.01% [27]. However, it remains unclear what percentage of previously obese individuals who undergo BS followed by live-donor nephrectomy will subsequently develop renal failure.…”
Section: Transplantation After Donor Bariatric Surgerymentioning
confidence: 99%